2018
DOI: 10.2175/106143017x15131012188079
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Exchanges Across the Sediment–Water Interface in a Bay of Lake Chaohu

Abstract: A year-long field investigation was carried out in the most heavily polluted bay of Lake Chaohu to assess the temporal exchanges of ammonium nitrogen (NH þ 4 -N) and soluble reactive phosphorus (SRP) across the sediment-water interface (SWI) and to provide remediation advises. Results showed that the monthly average fluxes of NH þ 4 -N and SRP were 31.38 and 6.98 mg m -2 d -1 , respectively, both of which were higher than those in many other hyper-eutrophic lakes around the world. The exchanges of NH þ 4 -N an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Component 3 was also found to correspond to marine humic-like components . Component 4 corresponds to terrestrially derived humic material . Due to the different dissolved organic matter concentrations of the dilute first and seventh surface water samples, the fluorescence intensities of components 1, 2, 3, and 4 identified by PARAFAC analysis should be normalized by the SUVA 254 , which indicates the practical fluorescent DOM compositions of the first and seventh surface water samples.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Component 3 was also found to correspond to marine humic-like components . Component 4 corresponds to terrestrially derived humic material . Due to the different dissolved organic matter concentrations of the dilute first and seventh surface water samples, the fluorescence intensities of components 1, 2, 3, and 4 identified by PARAFAC analysis should be normalized by the SUVA 254 , which indicates the practical fluorescent DOM compositions of the first and seventh surface water samples.…”
Section: Results and Discussionmentioning
confidence: 95%
“…67 Component 4 corresponds to terrestrially derived humic material. 68 Due to the different dissolved organic matter concentrations of the dilute first and seventh surface water samples, the fluorescence intensities of components 1, 2, 3, and 4 identified by PARAFAC analysis should be normalized by the SUVA 254 , which indicates the practical fluorescent DOM compositions of the first and seventh surface water samples. Figure 5b,c presents the corresponding fluorescence intensities of components 1, 2, 3, and 4 for the first and seventh surface water samples; it was observed that after treating the paddy constructed wetlands, the seventh-day surface water sample exhibited lower fluorescence intensities (5.7−88.2%) than the samples from the first day.…”
Section: ■ Results and Discussionmentioning
confidence: 99%